1991
DOI: 10.1210/endo-129-3-1429
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Mechanisms for Regulation of 3β-Hydroxysteroid Dehydrogenase/Δ5→Δ4-Isomerase, 17α-Hydroxylase/C17–20Lyase Cytochrome P450, and Cholesterol Side-Chain Cleavage Cytochrome P450 Messenger Ribonucleic Acid Levels in Primary Cultures of Mouse Leydig Cells*

Abstract: The regulation of mRNA levels for delta 5-3 beta-hydroxysteroid dehydrogenase/delta 5----delta 4-isomerase (3 beta HSD), 17 alpha-hydroxylase/C17-20 lyase cytochrome P450 (P450(17 alpha] and cholesterol side-chain cleavage cytochrome P450 (P450scc) was studied in primary cultures of mouse Leydig cells. Treatment of Leydig cells with 8-bromo-cAMP (cAMP) was essential for expression of P450(17 alpha) mRNA, but not for 3 beta HSD. Treatment with cAMP caused a decrease in basal levels of 3 beta HSD mRNA. The addit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
84
0

Year Published

1993
1993
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 134 publications
(91 citation statements)
references
References 13 publications
7
84
0
Order By: Relevance
“…The Leydig cell responds to glucocorticoids. Glucocorticoids have been found to directly inhibit the transcription of genes encoding testosterone biosynthetic enzymes such as cytochrome P450-dependent cholesterol side chain cleavage enzyme, and cytochrome P450-dependent 17α-hydroxylase/C 17 -C 20 lyase [16,22]. Cholesterol transporting protein steroidogenic acute regulatory protein (StAR) gene is also repressed by glucocorticoids [23].…”
Section: Stress and Leydig Cell Functionmentioning
confidence: 99%
“…The Leydig cell responds to glucocorticoids. Glucocorticoids have been found to directly inhibit the transcription of genes encoding testosterone biosynthetic enzymes such as cytochrome P450-dependent cholesterol side chain cleavage enzyme, and cytochrome P450-dependent 17α-hydroxylase/C 17 -C 20 lyase [16,22]. Cholesterol transporting protein steroidogenic acute regulatory protein (StAR) gene is also repressed by glucocorticoids [23].…”
Section: Stress and Leydig Cell Functionmentioning
confidence: 99%
“…Although the molecular mechanisms by which Gc decrease steroidogenesis have not been entirely defined, numerous studies have shown that Gc can inhibit expression of enzymes involved in testosterone biosynthesis such as Star, Cyp11a1, Cyp17a1, Hsd3b and Hsd17b3 (Hales & Payne 1989, Payne & Sha 1991, Wang et al 2000, Huang & Shirley 2001, Schwarzenbach et al 2003, Badrinarayanan et al 2006, Fon & Li 2007. Interestingly, variations in serum Gc content have no significant effect on circulating levels of LH and on its binding properties to its receptor, indicating that Gc repressive effects on Leydig cell steroidogenic capacity are not mediated by an indirect effect on pituitary LH production (Orr & Mann 1990, Orr et al 1994, Gao et al 1996.…”
Section: Introductionmentioning
confidence: 99%
“…The intra-testicular mechanism by which digoxin modulates steroidogenesis has not been well-de®ned, but a number of in vitro studies have shown that many compounds (e.g. lead or aminoglutethimide) may directly or indirectly target the enzymes required for the biosynthesis of testosterone in Leydig cells, including cytochrome P450 scc , P450 c 17, 3b-HSD, and 17-KSR (Payne & Sha, 1991;Thoreux et al, 1995).…”
Section: Introductionmentioning
confidence: 99%